Condition Factors and Length-Weight Relationships of Fifteen Important Fish Species in the Estuary of Manado Bay Indonesia - Manu, Gaspar; Bataragoa, Nego E.; Mandagi, Stephanus V.; Dauhan, Dulce Maria; Sampe, Ayumi Angraini (Sam Ratulangi University, 2023)
This research aims to analyze condition factors and growth patterns of estuary fish in Manado Bay. Sampling was carried out at the river estuary in Manado Bay, the Pineleng River in Bahu, the Sario River estuary in Sario, the Tondano River estuary in Sindulang, and the Bailang River estuary in Tumumpa. Sampling was carried out in June and July 2023 in the new moon and full moon phases at each river mouth. The fishing gear uses a beach seine 20 m long with a net height of 2 m. Analysis of condition factors and growth patterns using a length-weight relationship approach. Fulton's Condition Factor: K=100W/L3 Where K is the condition factor, W is the weight of the fish and L is the length of the fish (total length). Relative condition factor: Kn=W/Ŵ, where W is the weight of the fish and Ŵ is the estimated weight of the fish from the analysis of the length-weight relationship. Allometric and isometric growth patterns with length-weight relationship analysis: W=aLb where W is the weight of the fish (g), L is the length of the fish (cm), a and b are constants. During the research, 43 fish species were obtained and 15 of them were classified as important species whose presence was ≥1% relative abundance. Fulton's K obtained ranged from 0.69-1.76, the lowest species was 0.69 Stolephorus commersonnii and the highest was 1.76 Neovespicula depressifrons. The Kn value obtained for almost all species was ≈ 1.0, except for Sillago sihama, which was much smaller, namely 0.77. The value of the constant b relationship between length and weight varied between 2.22 in Caranx ignobilis and 3.9 in Ambassis gymnocephalus. The growth pattern is isometric for six species, negative allometric for four species, and positive allometric for five species. Keywords: Species, condition, allomotric, isomatric. Abstrak Penelitian ini bertujuan untuk manganalisis factor kondisi dan pola pertumbuhan ikan muara sungai di Teluk Manado. Pengambilan sampel dilakukan pada muara sungai di teluk Manado, Sungai Pineleng di Bahu, muara Sungai Sario di Sario, muara Sungai Tondano di Sindulang dan muara Sungai Bailang di Tumumpa. Sampling dilakukan pada bulan Juni dan Juli fase bulan baru dan bulan purnama pada masing-masing muara sungai. Alat tangkap menggunakan pukat pantai panjang 20 m dengan tinggi jaring 2 m. Analisis faktor kondisi dan pola pertumbuhan dengan pendekatan hubungan panjang-berat. Fulton’s Condition Factor: K=100W/L3 Di mana K adalah fator kondisi, W berat ikan dan L panjang ikan (panjang total). Faktor kondisi relative: Kn=W/Ŵ, di mana W adalah berat ikan dan Ŵ adalah berat ikan yang diduga dari analisis hubungan panjang-berat. Pola pertumbuhan allometrik dan isometrik dengan analisis hubungan panjang-berat: W=aLb dimana W adalah berat ikan (g), L panjang ikan (cm), a dan b adalah konstanta. Selama penelitian diperoleh 43 speses ikan dan 15 diantaranya tergolong speses penting yang kehadirannya ≥1% kelimpahan relatif. Fulton’s K diperoleh berkisar antara 0,69-1,76 spesies terendah 0,69 Stolephorus commersonnii dan tertinggi 1,76 Neovespicula depressifrons. Kn diperoleh hampir seluruh spesies nilai ≈ 1,0 kecuali Sillago sihama jauh lebih kecil yakni 0,77. Nilai konstatnta b hubungan panjang berat berfariasi antara 2,22 pada Caranx ignobilis dan 3,9 pada Ambassis gymnocephalus. Pola pertumbuhan isometrik enam spesies, allometrik negatif empat spesies dan allometrik positif lima spesies. Kata Kunci: Spesies, kondisi, almotrik, isomatrik.